Procalcitonin: changes and outcomes in pediatric sepsis at Chiang Mai University Hospital - K, Sunkonkit; S, Chanyutthana; S, Reungrongrat (Biomedical Sciences and Clinical Medicine, 2019)
Objectives Among a large array of laboratory tests for identifying sepsis, procalcitonin (PCT) has emerged as the leading biomarker for indicating sepsis accurately and in a timely manner. Our study aimed to characterize the change in PCT levels in pediatric sepsis cases and to determine the association with mortality, length of stay (LOS) in the pediatric ICU, and PRISM III score. Methods In this prospective observational study, pediatric patients diagnosed with sepsis and septic shock were enrolled. Demographic information, laboratory data and PCT levels at 0-24 hours and at 72-96 hours after admission were collected. PRISM III scores were assessed and 28-day mortality and LOS were recorded. Results Sepsis severity in the 58 children enrolled (median age 14.5 months, range 1-180 months) was classified as both sepsis (n=19, 32.7%) and septic shock (n=39, 67.2%). Respiratory tract infection was the most common cause. We found that a PCT level of 1.38 ng/mL can be used to distinguish between sepsis and septic shock with a sensitivity of 76.9% and a specificity of 68.4%. A reduction in PCT of less than 15% following treatment was associated with a higher mortality rate (OR 70.4, 95% CI, 7.23-685.08; p <0.001), but was not associated with LOS in the pediatric intensive care unit (PICU) or PRISM III score. Conclusion PCT level can be used to classify sepsis severity. A reduction in PCT level of 15% or more within 72-96 hours after treatment is associated with an improved survival rate, but is not associated with LOS in PICU or with PRISM III score.